Cover Feature: Enhancing Photostability of a Coumarin Dye by Self‐inclusion into a Cyclodextrin Cavity in Aqueous Solution and Living Cells (Asian J. Org. Chem. 12/2020). Issue 12 (7th December 2020) - Shigemitsu, Hajime; Matsuda, Keigo; Mori, Tadashi; Nakatsuji, Hirotaka; Matsusaki, Michiya; Kida, Toshiyuki
Abstract : Photostable organic dyes are required for long‐time or super‐resolution bioimaging. In this work, an effective improvement of photostability of a coumarin dye (Pacific Blue (PB )) is demonstrated by steric protection using a cyclodextrin. The PB ‐conjugated cyclodextrin (PB‐CD ) showed suppression of photodegradation and reactive oxygen species (ROS) generation during photoirradiation as compared to PB . The effects afford an improvement of photostability of PB dye. Finally, the photostability of PB‐CD was evaluated using confocal laser scanning microscopy (CLSM) and a significant improved effect was proven even in living cells. More information can be found in the Communication by Hajime Shigemitsu, Toshiyuki Kida, et al.